Identification of Kic1p and Cdc42p as Novel Targets to Engineer Yeast Acetic Acid Stress Tolerance - Chen, Hong-Qi; Xing, Qi; Cheng, Cheng; Zhang, Ming-Ming; Liu, Chen-Guang; Champreda, Verawat; Zhao, Xin-Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Robust yeast strains that are tolerant to multiple stress environments are desired for efficient biorefinery. Our previous studies revealed that zinc sulfate serves as an important nutrient for stress tolerance of budding yeast Saccharomyces cerevisiae. Acetic acid is a common inhibitor in cellulosic hydrolysate, and the development of acetic acid tolerant strains benefit lignocellulosic biorefinery. In this study, comparative proteomic studies were performed using S. cerevisiae cultured under acetic acid stress with or without zinc sulfate addition, and novel zinc-responsive proteins were identified. Among the differentially expressed proteins, the protein kinase Kic1p and the small rho-like GTPase Cdc42p, which is required for cell integrity and regulation of cell polarity, respectively, were selected for further studies. Overexpression of KIC1 and CDC42 endowed S. cerevisiae with faster growth and ethanol fermentation under the stresses of acetic acid and mixed inhibitors, as well as in corncob hydrolysate. Notably, the engineered yeast strains showed a 12 h shorter lag phase under the three tested conditions, leading to up to 52.99% higher ethanol productivity than that of the control strain. Further studies showed that the transcription of genes related to stress response was significantly up-regulated in the engineered strains under the stress condition. Our results in this study provide novel insights in exploring zinc-responsive proteins for applications of synthetic biology in developing robust industrial yeast.